Increased Glucose Transport–Phosphorylation and Muscle Glycogen Synthesis after Exercise Training in Insulin-Resistant Subjects - Perseghin, Gianluca; Price, Thomas B; Petersen, Kitt Falk; Roden, Michael; Cline, Gary W; Gerow, Karynn; Rothman, Douglas L; Shulman, Gerald I (The New England journal of medicine, 1996)
First-degree relatives of patients with non-insulin-dependent diabetes mellitus (NIDDM) have a lifetime risk of diabetes of approximately 40 percent. 1 In these relatives, insulin resistance is the best predictor of the development of diabetes and probably plays an important part in its pathogenesis. 2 – 4 The most important site of peripheral insulin resistance is the skeletal muscle, and in this tissue there are several steps involved in insulin-mediated glucose uptake in which insulin resistance might occur (Figure 1). Previous studies using carbon-13 nuclear magnetic resonance ( 13 C NMR) spectroscopy to measure the glycogen content of muscle demonstrated that a defect in insulin-stimulated . . .